Activated platelet aggregation is transiently impaired also by a reduced dose of protamine. (2nd November 2019) - Olsson, A.; Alfredsson, J.; Thelander, M.; Svedjeholm, R.; Berglund, J. Sanmartin; Berg, S.
Abstract: Objectives: Protamine reduces platelet aggregation after cardiopulmonary bypass (CPB). We studied the inhibitory effect of a reduced protamine dose, the duration of impaired platelet function and the possible correlation to postoperative bleeding. Design: Platelet function was assessed by impedance aggregometry in 30 patients undergoing cardiac surgery with CPB at baseline, before protamine administration, after 70% and 100% of the calculated protamine dose, after 20 minutes and at arrival to the intensive care unit. Adenosine diphosphate (ADP), thrombin receptor activating peptide-6 (TRAP), arachidonic acid (AA) and collagen (COL) were used as activators. Blood loss was measured during operation and three hours after surgery. Results are presented as median (25th–75th percentile). Results: Platelet aggregation decreased markedly after the initial dose of protamine (70%) with all activators; ADP 89 (71–110) to 54 (35–78), TRAP 143 (116–167) to 109 (77–136), both p < .01; AA 25 (16–49) to 17 (12–24) and COL 92 (47–103) to 60 (38–81) U, both p < .05. No further decrease was seen after 100% protamine. The effect was transient and after twenty minutes platelet aggregation had started to recover; ADP 76 (54–106), TRAP 138 (95–158), AA 20 (10–35), COL 70 (51–93) U. Blood loss during operation correlated to aggregometry measured at baseline and after protaminization. Conclusions: Protamine after CPB induces a marked decrease in platelet aggregation already at a protamine-heparin ratio of 0.7:1. The impairment seems to be transient and recovery had started after 20 minutes.